Coaching Conversations in Early Childhood Programs. Issue 4 (October 2015) - Jayaraman, Gayatri; Marvin, Christine; Knoche, Lisa; Bainter, Sue
<x xml:space="preserve">Abstract</x> Studies to date have linked early childhood (EC) coaching to child, family, and teacher outcomes but have not investigated "what" is happening in a coaching conversation. This exploratory study specifically unpacks nuances associated with the coaching conversation process and associations between the EC coaches' behaviors and coachees' participation during conversations. The results highlight conversation behaviors used by both EC coaches and coachees and how these behaviors may be associated with each other in building partnerships and promoting collaborative practices. The conversational behaviors of 24 EC coach–coachee dyads were investigated by reviewing videotaped sessions of their meetings using a reliable Early Childhood Coaching Conversations coding system. Results indicated much variability in the use of conversation behaviors. Bivariate correlations provided a hint of possible conversation behaviors associated with relationship building and a "shared ownership" process during coaching conversations. Implications for future work in research and practice are discussed.